Ekspresi Etnik Dalam Kapata Masyarakat Alifuru di Maluku Tengah (Kajian Etnopuitika) - Pattipeiluhu, Lisse; Yuwana, Setya; Muhsyanur, Muhsyanur (ELite Journal : International Journal of Education, Language and Literature, 2018)
Kapata is oral literature which is pronounced in the form of poetry or sung with or without using a melody. This study aims to describe (1) the relativity of language and culture in the Kapata community of Alifuru in Central Maluku; (2) poetic structure in the Kapata of the Alifuru community in Central Maluku. The approach in this study is qualitative with ethnographic studies. The data source in this study is the Central Maluku community who understands Kapata. The data in this study is the Kapata that has been translated. The results in the study show that: (1) the relativity of language and culture in the Kapata of the Alifuru community, as a form of expressing cultural values contained in the Kapata of the Alifuru community. (2) the poetic structure of the Alifuru community as a form of poetic arrangement that is in the Kapata, thus the poetic arrangement will be seen through pronunciation pronounced by humans through vowels, diphthongs and consonants in chanting the Kapata. The results of this study can benefit the community in preserving uniqueness area in the Kapata domain. Keywords: language relativity, cultural relativity, poetic structure, Kapata.